2017
DOI: 10.3233/cbm-170388
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Knockdown of lncRNA CCAT2 inhibits endometrial cancer cells growth and metastasis via sponging miR-216b

Abstract: To conclude, these results demonstrated lncRNA CCAT2 was highly expressed in endometrial cancer tissues. Knockdown of CCAT2 inhibited cell growth and metastasis of endometrial cancer cells by sponging miR-216b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…20 Previous studies have proved that CCAT2 knockdown significantly inhibits the migration and invasion of MKN45 cells (GC), 10 LCC9/MCF-7 cells (breast cancer), 21 and HEC-1-A/RL95-2 cells (endometrial cancer). 22 In this study, we found that siRNA-CCAT2 transfection significantly decreased the numbers of migrant and invasive cells. Our findings are just consistent with previous studies, and further illustrate that silencing of CCAT2 inhibits the migration and invasion of GC cells.…”
Section: Discussionmentioning
confidence: 53%
“…20 Previous studies have proved that CCAT2 knockdown significantly inhibits the migration and invasion of MKN45 cells (GC), 10 LCC9/MCF-7 cells (breast cancer), 21 and HEC-1-A/RL95-2 cells (endometrial cancer). 22 In this study, we found that siRNA-CCAT2 transfection significantly decreased the numbers of migrant and invasive cells. Our findings are just consistent with previous studies, and further illustrate that silencing of CCAT2 inhibits the migration and invasion of GC cells.…”
Section: Discussionmentioning
confidence: 53%
“…[2017] also provided evidence that miR‐216b inhibited glioma cell migration and invasion through suppression of FOXM1. In endometrial cancer, knockdown of lncRNA CCAT2 inhibited cell growth and metastasis via sponging miR‐216b [Xie et al., ]. The study performed by Yao et al.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [2017] also provided evidence that miR-216b inhibited glioma cell migration and invasion through suppression of FOXM1. In endometrial cancer, knockdown of lncRNA CCAT2 inhibited cell growth and metastasis via sponging miR-216b [Xie et al, 2017]. The study performed by Yao et al [2018] showed that miR-216b suppressed colorectal cancer proliferation, migration and invasion by targeting SRPK1.…”
Section: Research Articlementioning
confidence: 99%
“…CCAT2, as a novel oncogene, is located in the hotspot of tumour-related rs6983267 SNP, which promotes the occurrence and development of kinds of cancers by affecting Wnt and TGF-b signalling pathways [9,19]. Such as Xie et al reported that CCAT2 was overexpressed in endometrial cancer and knockdown of CCAT2 inhibited endometrial cancer cells growth and metastasis via sponging miR-216b [20]. Ruan et al also demonstrated that CCAT2 was able to promote the progression of OSA by enhancing cell proliferation via GSK3b/b-catenin signalling pathway [21].…”
Section: Discussionmentioning
confidence: 99%